A copula-based sensitivity analysis method and its application to a North Sea sediment transport model. (June 2018) - Ţene, Matei; Stuparu, Dana E.; Kurowicka, Dorota; El Serafy, Ghada Y.
Abstract: This paper describes a novel sensitivity analysis method, able to handle dependency relationships between model parameters. The starting point is the popular Morris (1991) algorithm, which was initially devised under the assumption of parameter independence. This important limitation is tackled by allowing the user to incorporate dependency information through a copula. The set of model runs obtained using latin hypercube sampling, are then used for deriving appropriate sensitivity measures. Delft3D-WAQ (Deltares, 2010) is a sediment transport model with strong correlations between input parameters. Despite this, the parameter ranking obtained with the newly proposed method is in accordance with the knowledge obtained from expert judgment. However, under the same conditions, the classic Morris method elicits its results from model runs which break the assumptions of the underlying physical processes. This leads to the conclusion that the proposed extension is superior to the classic Morris algorithm and can accommodate a wide range of use cases. Highlights: The widely used Morris algorithm is extended by relaxing the assumption of independence between model parameters. Dependencies are specified using a copula, thus enabling arbitrarily complex relationships between parameters. The method inherits the advantages of the classic Morris method and is equivalent to it when the independence copula is used. The new method is compared to the classic Morris algorithm on the Delft3D-WAQ sediment transport model. The MATLAB code, used to generate the presented sensitivity results, is made openly available.